2017
DOI: 10.1002/gea.21670
|View full text |Cite
|
Sign up to set email alerts
|

Bronze Age settlement mounds on the Colchian plain at the Black Sea coast of Georgia: A geoarchaeological perspective

Abstract: Situated between the Enguri and Khobistskali rivers, more than 30 settlement mounds (locally named Dikhagudzuba) provide evidence for a relatively densely populated landscape in the coastal lowlands of western Georgia during the Bronze Age. Compared to older mounds in eastern Georgia and other regions, these mounds differ not only in age but also in their average size and spatial distribution. Based on the interpretation of nine sediment cores, drone survey and structure‐from‐motion photogrammetry techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…These conclusions correlate well with the geoarchaeological research on three settlement mounds that were recently studied by scientists from the Ilia State University (Tbilisi, Georgia) and the University of Cologne (Germany) (Laermanns et al, 2018b). The results indicate that the mounds of the Colchian plain were intentionally accumulated rather than passively evolved.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…These conclusions correlate well with the geoarchaeological research on three settlement mounds that were recently studied by scientists from the Ilia State University (Tbilisi, Georgia) and the University of Cologne (Germany) (Laermanns et al, 2018b). The results indicate that the mounds of the Colchian plain were intentionally accumulated rather than passively evolved.…”
Section: Introductionsupporting
confidence: 85%
“…For the first time, this study offers a comprehensive summary of the Georgian literature on the Colchian Dikhagudzuba mounds. It supplies additional information about the mounds' internal structure, spatial extent and distribution to the first research results of Laermanns et al (2018b). By using vibracores taken on the top, the slope, and in the direct vicinity of one of the studied mounds and granulometrical and geochemical analyses, different stratigraphic layers were determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People spread from the foothills into the plain where the oldest settlement sites of Ontsakoshia (Janelidze and Tatashidze, 2010) and Ispani (Connor et al, 2007;de Klerk et al, 2009) date back to the transition between the Chalcolithic and the early Bronze Age in the mid-third millennium BCE. Since the early Bronze Age settlement mounds in the northern part of the Colchis have yielded evidence for the evolving Colchian culture (Lordkipanidze, 1991;Sens, 2009;Laermanns et al, 2017b). The region experienced its heyday between the sixth and fourth centuries BCE under the Kingdom of Colchis -a time of intensive trade contact with (mainly Milesian) Greek merchants, who had founded several colonies along the Colchian Black Sea coast (Sens, 2009;Gamkrelidze, 2012).…”
Section: Human Occupationmentioning
confidence: 99%
“…the area between the rivers Supsa and Enguri, Fig. 1) for palaeoenvironmental and geoarchaeological studies has been shown only in the very recent past by elucidating the mid-Holocene to late Holocene development of the Rioni delta (Laermanns et al, 2017a) and presenting new data on the evolution of Bronze Age settlements (Laermanns et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%